Efficacy of Conbercept in the Treatment of Choroidal Neovascularization Secondary to Pathologic Myopia - Lu, Hui; Yue, Tao; Liu, Na; Wang, Zuo-Fen; Zhai, Gai-Xia; Mi, Dong-Ming; Zhang, Jing; Wang, Shao-Peng (Frontiers in Medicine, 2021)
Purpose: To observe the clinical efficacy of conbercept in the treatment of choroidal neovascularization (CNV) secondary to pathologic myopia. Methods: We used retrospective analysis of the clinical data of 20 patients (24 eyes) with pathologic myopia choroidal neovascularization (PM-CNV). All patients were treated with intravitreal injection of conbercept 0.5mg (0.05ml), a vascular endothelial growth factor (VEGF) receptor fusion protein, and all patients completed at least six months of follow-up. Fundus, best corrected visual acuity (BCVA), fundus fluorescein angiography (FFA), optical coherence tomography (OCT), multifocal electroretinogram (mfERG) were assessed before and after treatment. Primary outcome was the functional change in amplitude by mfERG and secondary outcome was the structural change in central macular thickness（CRT） by OCT. The CNV area, leakage of CNV lesions, ocular and systemic adverse events were observed before and after treatment. Results: The BCVA were 64.33±10.83 letters, 65.42±11.24 letters, 67.67±7.07 letters after treatment 1 month, 3month, 6month respectively, which showed improvement compared with the baseline (P<0.05). The CRT decreased significantly from 308.50±45.48 μm to 219.63±30.27 μm, 221.33±40.65 μm, 220.96±33.09 μm after treatment 1 month, 3month, 6month respectively(P<0.05). The P1 response of mfERG amplitude improved from 40.71±9.69 nv/deg2 to 50.67±9.48 nv/deg2, 54.92±8.45 nv/deg2, 55.67±6.74 nv/deg2 after treatment 1 month, 3month, 6month respectively (P<0.05). After 6 months of treatment, the leakage of CNV lesions disappeared in 20 (83.3%) eyes, and the leakage area of CNV lesions was significantly reduced in 4 (16.7%) eyes. Conclusion: The intravitreal injection of conbercept significantly reduced CRT and the CNV area, inhibited the leakage of CNV, improved the BCVA, increased the response of mfERG amplitude, and restored the retinal function. The intravitreal injection of conbercept can change the morphology and function of the macular in PM-CNV, which is safe and effective for the treatment of PM-CNV.